Phase‐Controlled Synthesis of Monolayer Ternary Telluride with a Random Local Displacement of Tellurium Atoms. Issue 23 (17th April 2019) - Tang, Bijun; Zhou, Jiadong; Sun, Pingping; Wang, Xiaowei; Bai, Lichun; Dan, Jiadong; Yang, Jiefu; Zhou, Kun; Zhao, Xiaoxu; Pennycook, Stephen J.; Liu, Zheng
Abstract: Alloying 2D transition metal dichalcogenides has opened up new opportunities for bandgap engineering and phase control. Developing a simple and scalable synthetic route is therefore essential to explore the full potential of these alloys with tunable optical and electrical properties. Here, the direct synthesis of monolayer WTe2 x S2(1− x ) alloys via one‐step chemical vapor deposition (CVD) is demonstrated. The WTe2 x S2(1− x ) alloys exhibit two distinct phases (1H semiconducting and 1T ′ metallic) under different chemical compositions, which can be controlled by the ratio of chalcogen precursors as well as the H2 flow rate. Atomic‐resolution scanning transmission electron microscopy–annular dark field (STEM‐ADF) imaging reveals the atomic structure of as‐formed 1H and 1T ′ alloys. Unlike the commonly observed displacement of metal atoms in the 1T ′ phase, local displacement of Te atoms from original 1H lattice sites is discovered by combined STEM‐ADF imaging and ab initio molecular dynamics calculations. The structure distortion provides new insights into the structure formation of alloys. This generic synthetic approach is also demonstrated for other telluride‐based ternary monolayers such as WTe2 x Se2(1− x ) single crystals. Abstract : 2D ternary transitional metal dichalcogenides have been spotlighted recently. A one‐step chemical vapor deposition (CVD) method to synthesize monolayer WTe2 x S2(1− x ) alloys is reported. By tuning the ratio of chalcogen precursors and H2 flow rate, both semiconducting 1H and metallic 1T′ structures can be obtained. Local displacement of Te atoms from the original 1H lattice sites is also observed and studied.